2017
DOI: 10.1007/s13178-017-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Transgender Legal Name Change as a Potential Structural Intervention for Mitigating Social Determinants of Health Among Transgender Women of Color

Abstract: The purpose of this exploratory study was to examine the effects of legal name change on socioeconomic factors, general and transgender-related healthcare access and utilization, and transgender-related victimization in a sample of young transgender women (transwomen) of color. A cross-sectional group comparison approach was used to assess the potential effects of legal name change. A convenience sample of young transwomen enrolled in a no-cost legal name change clinic were recruited to complete a 30-minute in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 32 publications
1
42
0
1
Order By: Relevance
“…One example of a structural-level intervention is Hill et al, who explored employment among transgender women of color who had received no-cost legal name change support and found that those who had legally changed their name had greater odds of being employed. 59 Supporting transgender people with accessible legal name changes can address the everyday marginalization that occurs within various institutional systems due to cisgenderism, thereby directly impacting social factors, such as housing and jobs that Wilson et al 13 identified were connected to HIV risk.…”
Section: Discussionmentioning
confidence: 99%
“…One example of a structural-level intervention is Hill et al, who explored employment among transgender women of color who had received no-cost legal name change support and found that those who had legally changed their name had greater odds of being employed. 59 Supporting transgender people with accessible legal name changes can address the everyday marginalization that occurs within various institutional systems due to cisgenderism, thereby directly impacting social factors, such as housing and jobs that Wilson et al 13 identified were connected to HIV risk.…”
Section: Discussionmentioning
confidence: 99%
“…Community empowerment interventions among sex workers have been associated with increased condom use and a reduction in HIV risk [56][57][58], while legislation to facilitate gender affirmation may be more beneficial in reducing risk among TP [59,60]. Community empowerment interventions among sex workers have been associated with increased condom use and a reduction in HIV risk [56][57][58], while legislation to facilitate gender affirmation may be more beneficial in reducing risk among TP [59,60].…”
mentioning
confidence: 99%
“…Each KP group has specific issues that should be addressed in order to optimize their sexual health. Community empowerment interventions among sex workers have been associated with increased condom use and a reduction in HIV risk [56][57][58], while legislation to facilitate gender affirmation may be more beneficial in reducing risk among TP [59,60]. Other interventions may be appropriate for multiple groups.…”
mentioning
confidence: 99%
“…6,8,11,13,36,37 That legal name and gender marker changes were perceived barriers to employment and health services is supported by recent research documenting this relationship. 38 In addition, as our participants reported, access to transgender-affirming, knowledgeable, and affordable health care providers and mental health care is a significant challenge for transgender women and supported by existing research. 12,15,[39][40][41] Our study highlights several research gaps.…”
Section: Discussionmentioning
confidence: 61%